2022
DOI: 10.1007/s11192-022-04314-9
|View full text |Cite
|
Sign up to set email alerts
|

Why was this cited? Explainable machine learning applied to COVID-19 research literature

Abstract: Multiple studies have investigated bibliometric factors predictive of the citation count a research article will receive. In this article, we go beyond bibliometric data by using a range of machine learning techniques to find patterns predictive of citation count using both article content and available metadata. As the input collection, we use the CORD-19 corpus containing research articles—mostly from biology and medicine—applicable to the COVID-19 crisis. Our study employs a combination of state-of-the-art … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Computational modelling and machine learning are showing promise at citation prediction. 20 21 While we might not be as good as tomorrow’s machine learning, we are consoled that previously we demonstrated our editorial decision making could not be replaced by a non-qualified but experienced administrator. 28 …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Computational modelling and machine learning are showing promise at citation prediction. 20 21 While we might not be as good as tomorrow’s machine learning, we are consoled that previously we demonstrated our editorial decision making could not be replaced by a non-qualified but experienced administrator. 28 …”
Section: Discussionmentioning
confidence: 88%
“…19 Recently machine learning techniques have been used to find patterns that predict citation count with some success. 20 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some researchers suggested that the random forest (RF) model had a better prediction effect than the logistic regression model for predicting COVID-19 severity [ 55 ], a recent study noted that logistic regression is not always inferior to other ML algorithms [ 56 ]. It has better explanatory power than RF and the previously mentioned algorithms because they are a kind of “black-box” ML algorithms [ 57 ]. The Boruta algorithm was especially suitable for feature selection, although it is also a tree-based ML algorithm, which can be applied easily and modeled nonlinear relations well without much tuning [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods require a balanced dataset to perform well in per-class prediction accuracy and overly coarse classifications for domain-independent corpora. Recent research has shown that these methods perform well for domain-dependent tasks, particularly in classifying bio-medical scholarly documents [9]. Deep neural networks [10], such as convolutional and recurrent networks [11], have also been applied to classification tasks.…”
Section: Related Workmentioning
confidence: 99%